On the Time Resolution of Electrochemical Scanning Flow Cell Coupled to Downstream Analysis - Shkirskiy, Viacheslav; Speck, Florian; Kulyk, Nadiia; Cherevko, Serhiy (Journal of The Electrochemical Society, 2019)
Many of the recent advancements in the electrocatalysis research have been obtained by application of coupled electrochemistry/mass-spectrometry techniques. Representative example is the electrochemical flow cells coupled to inductively coupled plasma mass spectrometry (on-line ICP-MS) in electrocatalysis stability research. In this technique, unambiguous correlation of the concentration of dissolved species vs. potential/current represents a significant challenge due to different time scales of electrochemical and concentration transients. In this work, we address this issue by investigating the time resolution of the scanning flow cell (SFC). For this, residence time distribution (RTD) is estimated using Cu dissolution experiments. Both experiments and numerical simulations show that RTD can be closely approximated by a bi-Gaussian distribution with asymmetry arising from the mass transport of species in the outlet channel. Studying the influence of cell geometry and experimental conditions on RTD, it is found that the length of the outlet tubes of SFC should be as short as possible. Moreover, an optimum flow rate and angle between inlet and outlet channels are defined. To demonstrate practical applicability of our findings, obtained RTD was used to deconvolute previously reported platinum dissolution transients during cycling voltammetry. Such data are of high importance in mechanistic studies of platinum dissolution. (C) 2019 The Electrochemical Society.
CRIS-Team WoS Importer:2019-12-13